2011
DOI: 10.1007/s11431-011-4461-6
|View full text |Cite
|
Sign up to set email alerts
|

Vertical vibration characteristics of seated human bodies and a biodynamic model with two degrees of freedom

Abstract: Understanding the vibration characteristics of a seated human body is critical for evaluation and improvement of ride comfort of various passenger vehicles. There have been very little publications about the vibration characteristics of a seated Chinese human body. By using wide-band white noise excitations and a homemade seat sensor, vertical vibration tests were carried out on 28 volunteers. Apparent masses were obtained for each volunteer at a frequency range of 1-20 Hz for various excitation levels. A biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The proposed model used one degree-of-freedom to represent a human response. The previous study suggested that two, three and four degree-of-freedom to represent the biodynamic response of the human body [25][26][27][28][29][30][31]. Although the reported models provide a good fit at first and second resonance of the apparent mass, this is not the case for the second resonance of the seat transmissibility.…”
Section: Fitting the Model With The Experimental Datamentioning
confidence: 99%
“…The proposed model used one degree-of-freedom to represent a human response. The previous study suggested that two, three and four degree-of-freedom to represent the biodynamic response of the human body [25][26][27][28][29][30][31]. Although the reported models provide a good fit at first and second resonance of the apparent mass, this is not the case for the second resonance of the seat transmissibility.…”
Section: Fitting the Model With The Experimental Datamentioning
confidence: 99%
“…Fairley and Griffin 3 used random noise perturbations in which the frequency bandwidth was limited between 0.25 and 20 Hz, the acceleration spectral density was flat ± 5 % and the maximum magnitude was set as 1 m/s 2 root mean square (rms). Toward and Griffin 6,7 and Gao et al 10 used random noise perturbations with a duration of 60 s and a maximum acceleration magnitude of 1 and 2 m/s 2 rms, respectively. The frequency bandwidth was limited using 8-pole Butterworth filters between 0.13 and 40 Hz, 0.125 and 25 Hz, and 1 and 20 Hz, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al 8 and Kim et al 9 reported the vertical APMS for different sitting postures and seat designs. Gao et al 10 conducted similar experiments as Toward and Griffin. 7 A simple two-mass-lumped model was adopted to describe the vertical vibration characteristics of the seated human body.…”
Section: Introductionmentioning
confidence: 94%
“…In 2006, Liang et al analyzed and compared the different degrees of freedom model based on the experimental data of vertical vibration of European and American sitting posture [10]. In 2011, Gao et al obtained the basic parameters of human vibration based on sitting posture of few Chinese people [11]. The above results are the basic human body parameters biomechanics field, mainly used in automobile, machinery and other fields of medicine, cannot directly apply to the civil engineering structure model of the human body, but useful research ideas for other researchers.…”
Section: The Influence Of Crowd Load On Structural Dynamic Characterimentioning
confidence: 99%